Designing and implementation a web-based architecture for an examination timetabling system - Abdul Rahman, Syariza; Benjamin, Aida Mauziah; Omar, Mohd Faizal; Ramli, Razamin; Ku-Mahamud, Ku Ruhana; Abdul Jabbar, Waleed Khalid (Medwell Publishing, 2017)
In this study, we describe the design and implementation of a multi-objective examination timetabling system for the Universiti Utara Malaysia (UUM). As practice by most of the academic institutions, an examination timetable must be generated before the students sit for an examination. During the examination timetable generation, the assignment of the enrolled students of the offered courses to different times lots and rooms should be considered in order to avoid clashes. At the same time, clashes of lecturers are also considered in this study since lecturer’s attendance to the examination hall for the UUM case is compulsory for observing the progression of the examination. These requirements reflect the quality of the generated timetable. The aim of the developed system is to produce a conflict-free timetable while maximizing the satisfaction of preferences by students and lecturers. In addition of the automatic generation of the examination timetable, this study also emphasizes on the Graphical User Interface (GUI) of the system that enables the user to participate in the input, construction and modification of a timetable. In the construction and modification phase, the GUI enables the user to directly assign or reassign courses to times lots which is guided by heuristics. The results of the examination timetabling system were compared with the current timetable that was manually constructed and shows improvement in terms of its duration, quality and flexibility. The proposed system has simplified the activity of generating examination timetables since manual approach was considered during timetable generation.